FRAKTUR AND THERAPY MASSAGE LEGS, A DECREASE IN PAIN SCALE - Haslinda Damansyah (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The pain is a condition in the form of feeling that is not fun is very subjective because the feeling the pain different everyone in the scale or level and just the people that can explain or evaluate the pain that she had. Massage is the act of emphasis by hands on the soft tissue, usually the muscles tendos or ligamen without led to a shift or changes in the position of joints in order to reduce pain, produce relaxation,and or increase circulation. Research purposes : diketahuinya the effectiveness of therapy massage the foot of the decline in pain scale in patients in the surgery fraktur ekstremitas down in the room a scalpel in RSUD Type B in the health center Provincial Government Gorontalo. The study desingn used in this study is purposive sampling with the draft random assingnment control group pre test and post test with 30 of the respondents splits over 15 control group and 15 group intervention in patients in the surgery fraktur and data analysis using dependen test. The results : there was a decrease in pain scale after do therapy massage foot in the group intervention with p value 0,000 the suggestion therapy massage feet can be one of the intervension independent of nursing that can be done by the nurse to lose the intensity of the pain of the client in the surgery.